Roberto & me - Gutman, Dan (Gutman, Dan. Baseball card adventures., 2010)
Stosh travels back to 1969 to try to prevent the untimely death of Roberto Clemente, a legendary baseball player and humanitarian, but upon his return to the present, he meets his own great-grandson who takes him into the future, and what he finds there is more shocking than anything he has encountered in his travels to the past.